Feasibility of hemispatial neglect rehabilitation with virtual reality-based visual exploration therapy among patients with stroke: randomised controlled trial - Shin, Joon-Ho; Kim, Mingyu; Lee, Ji-Yeong; Kim, Mi-Young; Jeon, Yu-Jin; Kim, Kwanguk (Frontiers in Neuroscience, 2023)
Background: Hemispatial neglect (HSN) was diagnosed using a virtual reality-based test (FOPR test) that explores the field of perception (FOP) and field of regard (FOR). Here, we developed virtual reality-visual exploration therapy (VR-VET) combining elements from the FOPR test and visual exploration therapy (VET) and examined its efficacy for HSN rehabilitation following stroke. Methods: Eleven participants were randomly assigned to different groups, training with VR-VET first then waiting without VR-VET training (TW), or vice versa (WT). The TW group completed 20 sessions of a VR-VET program using a head-mounted display followed by four weeks of waiting, while the WT group completed the opposite regimen. Clinical HSN measurements (line bisection test [LBT], star cancellation test [SCT], Catherine Bergego Scale [CBS], CBS perceptual-attentional [CBS-PA], and CBS motor-explanatory [CBS-ME]) and FOPR tests (response time [RT], success rate [SR], and head movement [HM] for both FOP and FOR) were assessed by blinded face-to-face assessments. Results: Five and six participants were allocated to the TW and WT groups, respectively, and no dropout occurred throughout the study. VR-VET considerably improved LBT scores, FOR variables (FOR-RT, FOR-SR), FOP-LEFT variables (FOP-LEFT-RT, FOP-LEFT-SR), and FOR-LEFT variables (FOR-LEFT-RT, FOR-LEFT-SR) compared to waiting without VR-VET. Additionally, VR-VET extensively improved FOP-SR, CBS, and CBS-PA, where waiting failed to make a significant change. The VR-VET made more improvements in the left hemispace than in the right hemispace in FOP-RT, FOP-SR, FOR-RT, and FOR-SR. Conclusions: The observed improvements in clinical assessments and FOPR tests represent the translatability of these improvements to real-world function and the multi-dimensional effects of VR-VET training.